Analysis of the Mechanism of GuizhiFuling Wan in Treating Adenomyosis Based on Network Pharmacology Combined with Molecular Docking and Experimental Verification. (26th August 2022) - Shi, Yaxin; Zhang, Chengyuan; Wang, Xin; Wang, Zilu; Zhang, Yiran; Liu, Zhiyong; Wang, Xin; Shi, Wei
Abstract : Background . The effect of GuizhiFuling Wan (GFW) on adenomyosis (AM) is definite. This study aimed to explore the mechanism and key therapeutic targets of GFW in treating AM through network pharmacology combined with molecular docking and experimental verification. Materials and Methods . In network pharmacology, firstly, the active components of GFW, its drug, and disease targets were screened through several related public databases, and GFW-AM common targets were obtained after the intersection. Then, the biological function (Gene Ontology, GO) and pathway (Kyoto Encyclopedia of Genes and Genomes, KEGG) of GFW in treating AM were enriched and analyzed. Finally, the interaction and binding force between key components and key targets of GFW were verified by molecular docking. In the animal part, the effect of GFW on the expression of matrix metallopeptidase 2 (MMP-2), matrix metallopeptidase 9 (MMP-9), and vascular endothelial growth factor (VEGF) in mice with AM was observed by HE staining, ELISA, and immunohistochemistry. Results . In this study, 89 active components of GFW, 102 related targets, and 291 targets of AM were collected. After the intersection, 26 common targets were finally obtained. The key active compounds were baicalein, sitosterol, and β -sitosterol, and the key targets were MMP-2, MMP-9, and VEGF. GO and KEGG enrichment analyses showed that biological processes such as the positive regulation of vascular endothelial migration and signaling pathways such as TNF and HIF-1 were involved in regulating angiogenesis, invasion, and metastasis in AM. The molecular docking results showed that baicalein, β -sitosterol, and stigmasterol had better binding potential with MMP-2, MMP-9, and VEGF. The results of in vivo analysis showed that GFW could decrease the serum content and protein expression of MMP-2, MMP-9, and VEGF in mice with AM. Conclusions . GFW could reduce the expression of MMP-2, MMP-9, and VEGF, which might be an essential mechanism for GFW to inhibit the invasion and metastasis of ectopic tissues of AM.